Immigrants and unemployment in the European Community: From the Eyes of Natives - Ira N. Gang; Francisco L. Rivera-Batiz; Myeong-su Yun (Rutgers University, Department of Economics, 2002)
This paper examines whether a greater concentration of foreigners increases the likelihood of unemployment in local labor markets among citizens of the European Community. It provides the results of probit equations estimating the likelihood of employment in Europe as a function of a set of explanatory variables that include immigrant concentration in local labor markets. The estimates show a statistically significant, but weak, negative connection between the concentration of foreigners in a local labor market and the likelihood of employment among European citizens residing in that labor market. The results are shown to vary by country within the European Union.
Keywords: J38; J61; J64; 330; Europe; immigration; labor; local; unemployment